2016
DOI: 10.2119/molmed.2015.00254
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Autosomal Dominant or Recessive Methionine Adenosyltransferase I/III Deficiencies Based on Clinical and Molecular Studies

Abstract: Methionine adenosyltransferase (MAT) I/III deficiency can be inherited as autosomal dominant (AD) or as recessive (AR) traits in which mono-or biallelic MAT1A mutations have been identified, respectively. Although most patients have benign clinical outcomes, some with the AR form have neurological deficits. Here we describe 16 Korean patients with MAT I/III deficiency from 15 unrelated families identified by newborn screening. Ten probands had the AD MAT I/III deficiency, while six had AR MAT I/III deficiency.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…MATA1 deficiency is inherited either as autosomal-recessive or autosomal-dominant. Most MAT1A mutations give rise to autosomal recessive phenotypes, but several autosomal dominant mutations have also been observed, including c.776C > T, c.791G > A (Muriello et al, 2017), c.746G > A, and c.838G > A (Kim et al, 2016). With the exception of a few individuals with hypermethioninemia who present with abnormal neurological symptoms, most patients generally are free of major clinical manifestation.…”
Section: Discussionmentioning
confidence: 99%
“…MATA1 deficiency is inherited either as autosomal-recessive or autosomal-dominant. Most MAT1A mutations give rise to autosomal recessive phenotypes, but several autosomal dominant mutations have also been observed, including c.776C > T, c.791G > A (Muriello et al, 2017), c.746G > A, and c.838G > A (Kim et al, 2016). With the exception of a few individuals with hypermethioninemia who present with abnormal neurological symptoms, most patients generally are free of major clinical manifestation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a case series of 9 such patients reported that none of the patients had symptoms of MATI/III deficiency, all had normal development, tolerated normal diets, and had similar patterns of methionine levels that trended downward on follow-up [12]. Similarly, 6 patients with p.Arg248Gln and 1 patient with p.Gly280Arg in the heterozygous state had methionine levels that declined over time [13]. Both of these residues are predicted to be located at the dimerization interface.…”
Section: Discussionmentioning
confidence: 99%
“…However, discrepancies between the results of biochemical tests have often been observed, and biochemical enzyme assays are labor-intensive and tedious, and yield semiquantitative results. 2 17 In such cases, Sanger sequencing is the next step employed to confirm and differentiate the diagnosis. However, Sanger sequencing is also expensive and is hampered by the genetic heterogeneity of IMDs, which may result in delayed confirmation of diagnosis.…”
Section: Discussionmentioning
confidence: 99%